2011
DOI: 10.1186/1750-2187-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of polycomb group proteins in differentiated murine T helper (CD4<sup>+</sup>) cells

Abstract: BackgroundFollowing antigen recognition, naive T helper (Th; CD4+) cells can differentiate toward one of several effector lineages such as Th1 and Th2; each expressing distinctive transcriptional profiles of cytokine genes. These cytokines eventually instruct the strategy of the immune response. In our search for factors that propagate the transcriptional programs of differentiated Th cells, we previously found that Polycomb group (PcG) proteins, which are known as epigenetic regulators that maintain repressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 75 publications
4
31
0
Order By: Relevance
“…5D). This is in agreement with previous reports (13,28,29,31) and demonstrates that PRC2 has cellular functions that extend beyond what we have learned from its role at Hox genes. Importantly, our studies also suggest that despite a very good correlation of Jarid2 and Su(z)12 occupancies (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…5D). This is in agreement with previous reports (13,28,29,31) and demonstrates that PRC2 has cellular functions that extend beyond what we have learned from its role at Hox genes. Importantly, our studies also suggest that despite a very good correlation of Jarid2 and Su(z)12 occupancies (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…However, recent findings indicate that PRC2 (Jacob et al, 2011) and the Ezh2 methyltransferase subunit (Li et al, 2009) can also activate transcription (Simon and Kingston, 2013). In particular, H3K27me3 and H3S28p can coexist on the same histone molecule and H3K27me3S28 phosphorylation displaces PRC2 from the promoter (Gehani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(2,41) Several studies point to an important role of Ezh2 and H3K27me3 in multiple lineages of effector T cells. (14,17,20,25) Genome-wide mapping analysis revealed that repressive H3K27me3 marked genes associated with differentiation and maintenance of effector and memory T cells. (1,51) Most recently, we have demonstrated new and essential roles of Ezh2 in regulating inflammatory T cell responses in mice after allogeneic BMT.…”
Section: Introductionmentioning
confidence: 99%